Robust yarn electrodes for microbatteries with high areal capacity. (15th March 2019) - Park, Sarang; Lee, Byoung-Sun; Kang, Tae-Hyung; Choi, In-Suk; Yu, Woong-Ryeol
Abstract: This work reports the design strategy of mechanically robust yarn electrodes having high areal capacity (ca. 14 mAh/cm 2 ) as building blocks for microbatteries. Lithium iron phosphate (LiFePO4 ) was embedded into poly(acrylonitrile) nanofibers (NFs) via electrospinning. The obtained NFs were assembled into yarns via a yarning process, and were then thermally treated to produce carbon NF yarns. A hot-stretching process was used between the yarning and thermal treatment processes, improving the mechanical (tensile modulus of 1.03 GPa and strength of 38 MPa) and electrical (43.1 S/cm) properties of the yarn electrodes. The free-standing yarn electrodes with different mass loadings showed stable cycling performances with reasonable reversible capacity (ca. 112 mAh/g) up to 30 cycles. These mechanically robust and electrochemically excellent yarn electrodes could serve as building blocks for various structures in advanced microbatteries requiring high areal density. Graphical abstract: Unlabelled Image Highlights: Twisted nanofiber yarn was designed as a building block electrode for microbatteries. Yarn electrodes revealed excellent mechanical (tensile strength of 38 MPa) and electrical (43.1 S/cm) properties. Free-standing yarn electrodes showed high areal capacity (ca. 14 mAh/cm2) and cycling stability.